Beyond Israel and Aram: the archaeology and history of Iron Age communities in the central Levant - Kleiman, Assaf (Orientalische Religionen in der Antike, 2022)
Cover -- Title -- Preface -- Table of Contens -- 1. Introduction -- 1.1. On the Formation of the Territorial Kingdoms -- 1.2. In the Shadow of the Deuteronomistic History -- 1.3. Between Israel and Aram-Damascus -- 1.3.1. The 10th Century BCE -- 1.3.2. The Early 9th Century BCE -- 1.3.3. The Late 9th Century BCE -- 1.3.4. The 8th Century BCE -- 1.3.5. The Contribution of the Archaeological Research -- 1.4. Geographical and Chronological Frameworks -- 1.4.1. Defining the Central Levant -- 1.4.2. The Chronology of the Iron Age -- 1.5. Research Organization -- Part I. The Settlement History -- 2. The Lebanese Beqaa -- 2.1. Introduction -- 2.2. Key Sites -- 2.2.1. Tell Sugha -- 2.2.2. Tell Qasr Labwa -- 2.2.3. Baalbek -- 2.2.4. Tell Hizzin -- 2.2.5. Tell Hashbe -- 2.2.6. Tell el-Ghassil -- 2.2.7. Tell Barr Elyas -- 2.2.8. Tell Dayr Zanun -- 2.2.9. Tell Kamid el-Loz -- 2.2.10. Tell Dibbin -- 2.3. Regional Synthesis -- 3. The Hula Valley -- 3.1. Introduction -- 3.2. Key Sites -- 3.2.1. Tel Abel Beth-Maacah -- 3.2.2. Tel Dan -- 3.2.3. Tel Tannim -- 3.2.4. Kiryat Shmona South -- 3.2.5. Tel Anafa -- 3.2.6. Tel Hazor -- 3.2.7. Tel Ya'af -- 3.2.8. Tel Ya'af South -- 3.2.9. Rosh Pinna -- 3.2.10. Tel Nes -- 3.3. Regional Synthesis -- 4. The Sea of Galilee -- 4.1. Introduction -- 4.2. Key Sites -- 4.2.1. et-Tell/Bethsaida -- 4.2.2. Tel Kinrot -- 4.2.3. Tel Hadar -- 4.2.4. Tel Soreg -- 4.2.5. Tel Dover -- 4.2.6. Tel 'Ein Gev -- 4.3. Regional Synthesis -- 5. The Golan Heights -- 5.1. Introduction -- 5.2. Key Sites -- 5.2.1. Horvat Sa'ar -- 5.2.2. Mitzpe Golani -- 5.2.3. Bab el-Hawa -- 5.2.4. Metzad Yonathan -- 5.2.5. Rujm el-Hiri -- 5.2.6. Tell Shuqayyif -- 5.2.7. Tell Abu ez-Zeitun -- 5.2.8. Tel Nov -- 5.2.9. Khirbet 'Ain et-Taruq -- 5.3. Regional Synthesis -- Excursus A: The Cities of the Land of Garu and the Golan Heights -- 6. The Nuqra Plain.